2001
DOI: 10.1046/j.0007-1323.2001.01774.x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of antiplatelet therapy for the prevention of myocardial infarction, stroke or vascular death in patients with peripheral vascular disease

Abstract: Antiplatelet therapy reduces serious vascular events and vascular death in patients with PVD. For infrainguinal arterial surgery or balloon angioplasty the benefit remains unproven, but the number of trials to date is small. There is also evidence to support the use of antiplatelet drugs other than aspirin for the prevention of vascular events in those with PVD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
115
0
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(121 citation statements)
references
References 75 publications
(66 reference statements)
2
115
0
4
Order By: Relevance
“…Acetylsalicylic acid (ASA) had significant anti-platelet aggregation function [1] and it had been used for the prevention and treatment of AMI and thrombosis diseases from 1970s [2]. Evidence-based studies had proved that ASA could reduce the incidence rate of 25% of heart and brain and peripheral thromboembolic disease [3,4]. Especially for myocardial infarction and stroke, long-term use of the low-dose acetylsalicylic acid (ASA) could significantly reduce the incidence of this diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Acetylsalicylic acid (ASA) had significant anti-platelet aggregation function [1] and it had been used for the prevention and treatment of AMI and thrombosis diseases from 1970s [2]. Evidence-based studies had proved that ASA could reduce the incidence rate of 25% of heart and brain and peripheral thromboembolic disease [3,4]. Especially for myocardial infarction and stroke, long-term use of the low-dose acetylsalicylic acid (ASA) could significantly reduce the incidence of this diseases.…”
Section: Introductionmentioning
confidence: 99%
“…However, benefit in patients with established atherosclerosis without evidence of an ischemic event has recently been questioned [6]. Prior meta-analyses have yielded inconsistent findings with regard to the benefit of aspirin in PVD [7][8][9]. One reason for the disparate results of these meta-analyses is the heterogeneity of patients enrolled in the studies as well as the inclusion of studies with other antiplatelet agents, such as cilostazol or clopidogrel, as comparators.…”
Section: Introductionmentioning
confidence: 83%
“…RCTs showed mixed results but with a potential decreased risk of vascular events in patients on ASA in the perioperative period [46][47][48]. In contrast, the PEP trial, involving 13 356 patients undergoing hip surgery, demonstrated more cardiac ischaemic events (death due to ischaemic heart disease or nonfatal MI) in patients randomised to ASA versus placebo (HR 1.33, 95% CI 1.00-1.78) [49].…”
Section: Aspirinmentioning
confidence: 99%